Analysis of different levels of cognitive domain in undergraduate written short answer questions in Physiology: A descriptive study in Bangladesh - Rajwana, Jawairia; Ferdousi, Sultana; Amin, Nahid Farhana (Journal of Bangladesh Society of Physiologist, 2022)
Background: Teaching-learning and assessment of Physiology should be more organized because it builds the foundation for clinical science. A written question sheet on Physiology can be claimed ideal when it can assess the competence at different levels of cognitive domain of student’s learning. Objectives: The aim of the present study is to find out the prevalence of questions addressing different levels of cognitive domain in the first professional MBBS written examination on Physiology. Methods: This descriptive and retrospective type of study was conducted in the Department of Physiology, BSMMU, Dhaka, during the period of March 2020 to February 2021. A total 67 Short Answer Question(SAQ) sheets in the first professional MBBS examinations of the last five years of four public universities of Bangladesh were analyzed following revised Bloom’s Taxonomy. The frequency percent of questions addressing six levels of cognitive domain was manually calculated. Results: ‘Question-segments’ assessing remember level were greater than 80%, Whereas, ‘questionsegments’ assessing understand, apply and analyze level ranged between 11-13%,0.25-0.95% and 0.11-0.67% respectively in all the universities. No ‘question-segment’ was found addressing evaluate and create level of cognitive domain. Conclusion: From the results of this study, it may be suggested that there is almost absence of questions for assessment of student’s higher order thinking ability and most of the questions used, assessed the lowest level of cognition process in the first professional MBBS written examination on Physiology under four public universities of Bangladesh. J Bangladesh Soc Physiol. 2022, June; 17(1): 49-55